Al-Tafkīr al-Islāmī ‘an Taḥrīr al-Mar’ah bi Indūnīsiyā - Emzi Netri (Studia Islamika, 1997)
The generally weak position of women in Muslim  society  has given birth  to a movement and  thought  among  Indonesian  Muslims  concerning women's emancipation. Prominent figures have critized Muslim undersanding of women's position inherited from generation  to generation for  inferior and subordirate  position of women  in socicty. According to these figures,  Islam is God's mercy for all and, as such, Islam  cannot  possibly  treat men  as special while regarding women as having a lower status. Although  critical of how Islam understood women status,  their conceptualization  and articulation of the problem has differed according to the historical  period and context in question.DOI: 10.15408/sdi.v4i4.769